PROFIL DAN ANALISIS AKTIVITAS ANTIOKSIDAN DALAM EKSTRAK AIR MENIRAN YANG DIKERINGKAN DENGAN METODE YANG BERBEDA Profile and Analysis of Antioxidant Activity in Dried Meniran Water Extracts using Different Methods - Ai Sri Kosnayani; Liah Badriah; Asep Kurnia Hidayat; Muhammad Eka Asri Rizal (Media Gizi Indonesia, 2021)
Meniran (Phyllanthus niruri Linn.) is a medicinal plant that can reduce obesity status, hypoglycemic, hypotensive, and have antioxidant activity. Meniran has been long used as a medicinal plant, but its utilization in a form of water infusion is still rare. This research is a continuation study which aims to identify the biomolecules that have antioxidant activity in water infusion of meniran. The making of water infusion of meniran requires drying process, which can be done by room temperature drying and sun drying. Phenol and fl avonoid compounds in meniran are assumed to have antioxidant activity. Both compounds are easily oxidized and isomerized due to sun exposure. It is assumed that the drying method will aff ect the presence of phenol and fl avonoid compounds and its antioxidant activity. The study began with the process of sun drying and room temperature without direct sun exposure. Then the extraction process used water soxhlet by soxhlet extraction method. The extract was then tested qualitatively using the DPPH IC50 method. The results of the qualitative analysis with meniran color visualization are positive containing fl avonoids and phenols. The results of quantitative analysis of meniran which are dried by sun drying; fl avonoids 0.90% w/w and 1.65% w/w phenols, in samples stored at room temperature: 2.00% w/w fl avonoids and phenol 56.16% w/w. The antioxidant activity of IC50-DPHH in extract concentrations (2, 4, 6, 8, 10, 15, 20 ppm) of dried meniran at room temperature 18.48 ppm, sun drying cannot be determined.